2008
DOI: 10.1007/bf03340938
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Naming and Phonological Processing as Predictors of Reading and Spelling

Abstract: This study examined the relationships between the cognitive processes of rapid naming and phonological processing and various literacy skills. Variables measured and used in this analysis were phonological processing, rapid naming, reading comprehension, isolated and nonsense word reading, and spelling. Data were collected from 65 second-to-fifth grade children referred for learning difficulties. Regression analysis was performed to determine which of the cognitive processes was the strongest predictor of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Many researchers have shown strong, significant correlations between spelling ability and reading performance, ranging from .68 to .93, and have demonstrated the predictive powers of decoding and spelling performance on future reading and spelling abilities (Christo & Davis, 2008; Mehta, Foorman, Branum-Martin, & Taylor, 2005; Ritchey, 2008). Thus, encoding instruction and practice may offer insight into the types of knowledge individuals use to read and write unfamiliar words, providing a window to what students know about how words work (He & Wang, 2009; Joshi, Treiman, Carreker, & Moats, 2008; Stone, Siliman, Ehren, & Apel, 2005).…”
mentioning
confidence: 99%
“…Many researchers have shown strong, significant correlations between spelling ability and reading performance, ranging from .68 to .93, and have demonstrated the predictive powers of decoding and spelling performance on future reading and spelling abilities (Christo & Davis, 2008; Mehta, Foorman, Branum-Martin, & Taylor, 2005; Ritchey, 2008). Thus, encoding instruction and practice may offer insight into the types of knowledge individuals use to read and write unfamiliar words, providing a window to what students know about how words work (He & Wang, 2009; Joshi, Treiman, Carreker, & Moats, 2008; Stone, Siliman, Ehren, & Apel, 2005).…”
mentioning
confidence: 99%
“…As for the design of the articles, it was found that a large part (13 studies) had a cross-sectional observational design (4,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and that the majority (21 studies) consisted of prospective and retrospective studies . In addition to these, three were considered pre-experimental (48)(49)(50) , addressing intervention programs.…”
Section: Analysis Of Selected Studiesmentioning
confidence: 99%
“…Regarding the scenario, most of the studies included in the review were carried out in a school setting (4,15,17,(19)(20)(21)25,27,32,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) and, to a lesser extent, in clinics (16,18,(23)(24)(28)(29)(30)33,(35)(36)(37)51) and one of them, in an outpatient clinic of a higher education institution (31) . Besides, there is a greater number with large samples studied and a substantial increase in the number of publications since 2009, reaching 80% of the scientific productions analyzed in this review.…”
Section: Analysis Of Selected Studiesmentioning
confidence: 99%
“…HOİ testlerinde sorun yaşayan öğrenciler genellikle okumada da sorun yaşarlar ve bu durum onların anlamalarını olumsuz etkiler (Decker ve Carboni, 2011). Özellikle sesli akıcı okumada HOİ'nin çok güçlü bir yordayıcı olduğu farklı çalışmalarla ortaya konmuştur (Christo ve Davis, 2008;Kasperski, Shany ve Katzir, 2016;Kim, Park ve Lombardino, 2015;Lipka, 2017;Papadopoulos, Spanoudis ve Georgiou, 2016). HOİ ve okuma arasındaki ilişkiyi daha da detaylandırmaya yönelik çeşitli önermeler ileri sürülmüştür.…”
Section: Hoi̇ Ve Okumaunclassified